EFEKTIVITAS PELATIHAN PEMBUATAN OVITRAP DI SANGGAR BELAJAR AMI KULIM PENANG MALAYSIA - Sukesi, Tri Wahyuni; Sa'dani, Olivi Sabilla; Rachmawati, Wiwik Suci; Fitri, Rika Yulianti (Universitas Ahmad Dahlan, 2024)
Dengue fever cases in Malaysia experienced a staggering surge of 150.7%, which presented a significant public health threat. One potential solution was to educate the populace about the use of Ovitrap as a means to regulate and diminish Aedes aegypti mosquito populations. A study was undertaken to evaluate the efficacy of teaching ovitrap construction at the Ami Kulim learning studio in Penang, Malaysia. The research employed a quasi-experimental approach, utilizing a one-group pretest-posttest design with a sample size of 24 children. Data analysis involved the utilization of average and Wilcoxon tests. Results unveiled a notable disparity in the comprehension of ovitrap production before and after the instructional sessions (p-value = 0.005). Further investigation indicated that 16 participants had enhanced their understanding, while 5 exhibited a decline, and 3 remained unchanged. Consequently, it was justifiable to conclude that there existed a substantial shift in the knowledge of ovitrap assembly following the training intervention